1994
DOI: 10.1046/j.1471-4159.1994.62020680.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Tyrosine Hydroxylase in the Locus Coeruleus of Suicide Victims

Abstract: The amounts of tyrosine hydroxylase protein in locus coeruleus from nine pairs of antidepressant-free suicide victims and age-matched, sudden-death control cases were determined by quantitative blot immunolabeling of cryostat-cut sections from the caudal portion of the nucleus . In each of the nine age-matched pairs, the concentration of tyrosine hydroxylase was greater in the sample from the suicide victim, with values ranging from 108 to 172% of the matched control value (x = 136%) . By contrast, there were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
3
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(73 citation statements)
references
References 22 publications
6
62
3
2
Order By: Relevance
“…Abnormalities that have been observed in the LC from human depressives (Klimek et al, 1997;Ordway et al, 1994aOrdway et al, , 1994bOrdway et al, , 2003Zhu et al, 1999) can be reproduced, in part, by chronic stress or pharmacological depletion of norepinephrine in rats (Cubells et al, 1995;Lee et al, 1983;Melia et al, 1992;Torda et al, 1985;U'Prichard et al, 1979;Wang et al, 1998;Zafar et al, 1997). Given that stress activates the LC in laboratory animals (Pavcovich et al, 1990), that chronic stress depletes norepinephrine in the LC (Weiss and Simson, 1986), and that stress is a common precipitator of depression in humans, it seems possible that depression may be associated with elevated excitatory input to the LC.…”
Section: Role Of Glutamatergic Signaling In Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormalities that have been observed in the LC from human depressives (Klimek et al, 1997;Ordway et al, 1994aOrdway et al, , 1994bOrdway et al, , 2003Zhu et al, 1999) can be reproduced, in part, by chronic stress or pharmacological depletion of norepinephrine in rats (Cubells et al, 1995;Lee et al, 1983;Melia et al, 1992;Torda et al, 1985;U'Prichard et al, 1979;Wang et al, 1998;Zafar et al, 1997). Given that stress activates the LC in laboratory animals (Pavcovich et al, 1990), that chronic stress depletes norepinephrine in the LC (Weiss and Simson, 1986), and that stress is a common precipitator of depression in humans, it seems possible that depression may be associated with elevated excitatory input to the LC.…”
Section: Role Of Glutamatergic Signaling In Depressionmentioning
confidence: 99%
“…Previous observations reveal that depression is associated with altered concentrations of several noradrenergic proteins in the LC. For example, elevated levels of tyrosine hydroxylase (TH) (Ordway et al, 1994a;Zhu et al, 1999), increased agonist binding to a 2 -adrenergic receptors (Ordway et al, 1994b(Ordway et al, , 2003, and reduced levels of norepinephrine transporters (Klimek et al, 1997) were previously reported in the LC from major depression and in suicide victims. Interestingly, depletion of norepinephrine or repeated stress in rats can increase TH expression, increase binding to a 2 -adrenergic receptors, and/or decrease binding to the norepinephrine transporter (Cubells et al, 1995;Lee et al, 1983;Melia et al, 1992;Torda et al, 1985;U'Prichard et al, 1979;Wang et al, 1998;Zafar et al, 1997).…”
Section: Introductionmentioning
confidence: 96%
“…Levels of monoamine neurotransmitters and metabolites (HPLC with electrochemical detection; Wilson et al 1994 (Ordway et al 1994;Zhong et al 1995), VMAT2 protein by quantitative blot immunolabeling using an affinity-purified antibody (Chemicon) raised against a previously described peptide (Erickson et al 1996), and ERK1/2 protein by quantitative blot immunolabeling (Ortiz et al 1995) were conducted as previously described.…”
Section: Brain Dissection and Neurochemical Analysesmentioning
confidence: 99%
“…Left side nuclei were used for other experiments. We have previously found no differences in right and left side biochemical or cellular data (37,41,42). Tissue blocks were then sectioned sequentially using a cryostat microtome (− 16°C ) in a transverse plane perpendicular to the floor of the fourth ventricle throughout the entire length of the LC beginning near its rostral end, collecting all tissue sections.…”
Section: Dissectionmentioning
confidence: 99%
“…Converging evidence from studies of the LC from postmortem depressed subjects and from catecholamine-depletion studies in living depressed subjects has provided compelling evidence that depression is associated with a deficit in noradrenergic transmission [12,36,39] Previous observations from postmortem studies have revealed that major depressive disorder (MDD) and suicide are associated with altered concentrations of several noradrenergic proteins in the LC. For example, elevated levels of tyrosine hydroxylase [42,69], increased agonist binding to α 2 -adrenergic receptors [40,43] and reduced levels of norepinephrine transporters [20] have been reported in the LC from MDD subjects and/or from suicide victims. Studies utilizing laboratory animals provide interesting insights into the possible basis for these postmortem findings.…”
Section: Introductionmentioning
confidence: 99%